O Enigma da Esfinge: A Emergência do Mito Ulisses na Arte e no Cinema Sob a interface Junguiana - Lopes, Adriana Goreti de Oliveira (2020)
This thesis has the objective to study the mythic narrative that is present in several arts, such as the movie, the literature and its connections with Analytical Psychology interfacing. It is about Ulysses’s journey, Homer’s and James Joyce’s work, the methodological assumption of the compared literature. The research is done by the theoretic objective of Homer ’s work, The Odyssey, the films o Brother, Where Art Thou? directed by the Brothers Joel and Ethan Coen in 2000. What is Brazil, in 1985, by Terry Giliam and Steppenwolf, directed by the American Fred Haines, in 1974. These movies belong to introverted genre. The last movie that will be analyzed is Bloom, all life in only one day. Ulysses’s Work adaptation, by James Joyce, in 2003, represented by the extroverted genre. Aby Warburg’s method image analyses (2015) called “iconographies” allows to show the image reappearance, his posthumous and dialectic life between myth and logo to illustrate the figure of the human condition going back to a past echo, through Ulysses drama, but Always bringing the zeitgeist, under a new textuality. As a result, it was used the theorycal body of Analytical Psychology of Carl Gustav Jung (2011) and Jungian authors as Hillman (2011), mythologist as Campbell (2007) and Kerényi (2015); the adaptation of the hero’s journey to the movie of Vogler (2015) and Canevacci (1990), the relation of this language to these bodies with the theorycal presupposition method of the Compared Literature, considering Nitrini and Coutinho’ s study (2003).